Irritable bowel syndrome and its associated factors in adolescents - Fillekes, Lara; Prayogo, Ari; Alatas, Fatima Safira; Hegar, Badriul (Paediatrica Indonesiana, 2014)
Background Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder. Increasing prevalences have been reported in Asian adolescent populations, however, there have been few reports on Indonesian adolescents. Objective To investigate the prevalence of IBS and associated factors among adolescents in Jakarta. Methods This cross-sectional study included senior high school students in a district of Jakarta. Students were asked to fill questionnaires based on the Rome III criteria for IBS. They were then divided into groups: those with IBS and those without IBS, for the purposes of comparison. Results Out of 232 adolescents (145 females and 87 males) with mean age of 16.06 (SD 0.91) years, 14 (6.0%) had IBS. Eleven out of 14 adolescents with IBS reported upper abdominal pain as well as periumbilical/lower abdominal pain. Irritable bowel syndrome was not associated with socioeconomic status, food and drink habits, the use of antibiotics, or scolding as a parental form of discipline. However, a significant higher proportion in the use of corporal punishment was found in IBS adolescents compared to the non-IBS (P=0.034). In addition, stress related to scolding, as a parental form of discipline was more likely to be found in the IBS group than in the non-IBS group (P=0.019). Conclusion The prevalence of IBS among adolescents in Jakarta is 6%, which is lower compared to those of other Asian countries. Corporal punishment at home and stress related to scolding at home are found to be associated with IBS.